Impact of AIS Implementation and HR Competence on Financial Reporting Quality in Indonesian Manufacturing Companies - Rusdiah Hasanuddin (Harmony Management: International Journal of Management Science and Business, 2024)
The quality of financial reporting has become increasingly important in the digital era, particularly for manufacturing companies facing complex operational challenges. The implementation of accounting information systems (AIS) and human resource competency are critical factors that may influence financial reporting quality. This study aims to examine the effect of accounting information systems implementation and human resource competency on the financial reporting quality of manufacturing companies listed on the Indonesia Stock Exchange (IDX). This quantitative study employed a survey design with primary and secondary data collection. The sample consisted of 150 manufacturing companies listed on IDX during 2020-2023, selected using purposive sampling. Data were collected through structured questionnaires distributed to finance managers and financial statement analysis. Multiple regression analysis was used to test the hypotheses. The findings indicate that accounting information systems implementation has a significant positive effect on financial reporting quality (β = 0.456, p < 0.01). Human resource competency also shows a significant positive effect on financial reporting quality (β = 0.387, p < 0.01). The simultaneous effect of both variables explains 68.7% of the variance in financial reporting quality (R² = 0.687, F = 165.42, p < 0.01). Both accounting information systems implementation and human resource competency significantly enhance financial reporting quality. Manufacturing companies should prioritize investing in advanced AIS technology and developing human resource competencies to improve their financial reporting quality.